Reconstructing the List of Returnees: A Text-Critical Solution to Ezra 2 ‖ Nehemiah 7 ‖ 1 Esdras 5 - Segal, Michael (Textus, 2023)
One of the earliest puzzles discussed in the textual history of the Hebrew Bible is the parallel lists and count of returnees in the Restoration period that appear in Ezra 2 ‖ Nehemiah 7 ‖ 1 Esdras 5, to which both traditional and critical commentators have turned their attention. These passages have raised multiple interpretive cruxes in the interpretation of the book of Ezra-Nehemiah, including contradictions between the different versions of the list, and their internal inconsistency. The current study offers a solution for both of these issues, based upon two independent arguments: (1) a proposed arithmetic methodology for determining the original numerical details of the entries to the list according to a maximalist principle. Using this method, the attested values for each entry are compared, allowing for the reconstruction of the list in a putative original form. (2) a text-critical analysis of the verses in which the total of the returnees is summarized (Ezr 2:64–65; Neh 7:66–67; 1 Esd 5:41), which expands the boundaries of those included in the total count. When the list is reconstructed by combining these insights, then we are left with an internally coherent, almost equation of the entries with the sum total.